Combined Korean Medicine Treatment of a Rare Case of Burst Fracture in an Elderly Patient with Kissing Spine - Eun-Young Park; Jong-Ho Choi; Hoo-In Jo; Soo-Kyung Lee; June-Haeng Lee; Sun-Woo Kang; Yoon-Jae Won; Sung-Ryul Choi; Yu-Jin Cho (MEDrang Inc., 2021)
A burst fracture refers to the fracture of the anterior and middle vertebral columns which are moving into the spinal canal causing neurological impairments, generally requiring surgical treatment. We herein report a rare case of burst fracture with kissing spine in a 90-year-old man who had severe lower back pain that worsened during back extension. Considering the surgical treatment risk, he was hospitalized at a Korean medicine hospital for 85 days and underwent combined Korean medicine treatments including pharmacopuncture, herbal medicine, chuna, deep-fascia meridian therapy, walking practice, and abdominal breathing. Based on patient-reported scales, his pain was alleviated, and his physical function improved. Furthermore, his range of motion and walking time increased. This case report suggests that combined Korean medicine treatments could be an effective alternative for patients with burst fracture who have surgery risks.